2005
DOI: 10.1080/02571862.2005.10634684
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships amongst macadamia varieties grown in South Africa as assessed by RAF markers

Abstract: Macadamia is an important horticultural crop of South Africa, and the major cultivars grown have a wide range of attributes. These cultivars originated from diverse backgrounds, but the genetic relatio'nships between them are unclear. Here we describe new insights into the genetic identity, relationships, and species composition of 38 varieties of macadamia representing the diversity currently available within the macadamia industry of South Africa. The varieties were surveyed with the DNA marker system, RAF (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
2
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 4 publications
6
45
2
7
Order By: Relevance
“…Recent development of DNA marker methodology (Aradhya et al 1998;Steiger 2003;Steiger et al 2003;Peace 2005;Peace et al 2005;Schmidt et al 2006) has assisted with the elucidation of genetic relationships in the domesticated germplasm. A review of published and unpublished literature identified over 900 cultivar names representing 500 apparently distinct genetic entities (Hardner and McConchie 1999).…”
Section: Germplasm Domesticationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent development of DNA marker methodology (Aradhya et al 1998;Steiger 2003;Steiger et al 2003;Peace 2005;Peace et al 2005;Schmidt et al 2006) has assisted with the elucidation of genetic relationships in the domesticated germplasm. A review of published and unpublished literature identified over 900 cultivar names representing 500 apparently distinct genetic entities (Hardner and McConchie 1999).…”
Section: Germplasm Domesticationmentioning
confidence: 99%
“…In addition, Hawaiian cultivars are responsible for much of the current world production (Hamilton and Fukunaga 1970;Allan 1989;Ito and Hamilton 1989;Stephenson 1990a;Peace et al 2005;Tay 2006). …”
Section: A Hawaiimentioning
confidence: 99%
See 1 more Smart Citation
“…*Autor para correspondência. II (PEACE et al, 2005). No Brasil, os trabalhos de melhoramento genético com a nogueiramacadâmia foram realizados, inicialmente, pelo Instituto Agronômico de Campinas (IAC), que visou, sobretudo, à seleção de cultivares produtivas e adaptadas às condições climáticas do Estado de São Paulo (SOBIERAJSKI et al, 2006;BASTOS et al, 2006).…”
Section: Introductionunclassified
“…No Havaí, foram lança-dos os cultivares de nogueira-macadâmia da série HAES, pelo Hawaii Agricultural Experiment Station, como 'Pahala' (HAES 788), 'Kau' (HAES 344), 'Keauhou' (HAES 246), 'Mauka' (HAES 741), 'Ikaika' (HAES 333), 'Kakea' (HAES 508), 'Keaau' (HAES 660), 'Makai' (HAES 800), 'Keauhou' (HAES 224), dentre outras de menor importância comercial (Peace et al, 2005).…”
Section: Introductionunclassified